Other-Focused Approach to Teaching. The Effect of Ethical Leadership and Quiet Ego on Work Engagement and the Mediating Role of Compassion Satisfaction - Buonomo, Ilaria; Farnese, Maria Luisa; Vecina, Maria Luisa; Benevene, Paula (Frontiers in Psychology, 2021)
Recent revisions of the Job Demands Resources (JDR) model acknowledged the importance of personal and organizational dimensions enriching job resources’ effect on work engagement. Consistently, this paper addresses the role of compassion satisfaction, as a job resource, on teacher work engagement, given the saliency of caring in teaching as a helping profession. Furthermore, quiet ego, as a personal dimension, and ethical leadership, as an organizational dimension, are studied as antecedents of compassion satisfaction. Overall, the study verifies with a Structural Equation Model whether and how compassion satisfaction mediates the relationships among work engagement, quiet ego, and ethical leadership. One hundred and eighty-eight Italian teachers took part in the study by completing four scales: the Ethical Leadership Scale, the Quiet Ego scale, the Professional Quality Of Life Questionnaire, and the Utrecht Work Engagement Scale – ultra-short version. The final model showed a good fit to the data: χ2(48) = 75.399, p = .007, CFI = 0.979, TLI = 0.971, RMSEA = 0.055 (90% CI = 0.029–0.078, p = .342), SRMR = 0.039. Findings showed that teachers’ compassion satisfaction is strongly related to their engagement at school, confirming that teachers’ care towards their students is an important resource supporting their engagement. Furthermore, compassion satisfaction totally mediates the relationship between quiet ego and work engagement (bDIRECT = ns, bINDIRECT = .327, p =.000). Such mediating path confirms recent expansions of the JDR model about the role of personal resources on job resources and, consequently, on work engagement and confirms the Conservation of Resources theory, stating that personal resources impact work outcomes. At the same time, compassion satisfaction does not mediate the relationship between ethical leadership and work engagement, so that ethical school leaders directly impact teachers’ work engagement. A possible reason for this finding relies on ethical leadership’s role in promoting higher school life participation as a community. More theoretical and practical implications are described in the paper.